Shakespeare and the Greek Romance : A Study of Origins - Gesner, Carol, 1922- (Book collections on Project MUSE., 1970)
This is the first study to relate the Greek romances to Elizabethan drama. It focuses upon the Greek romance materials in Shakespeare's plays to clarify the background of his art and to illuminate the relationship between the two literatures. The Greek romance tradition is described historically and traced through the works of Boccaccio and Cervantes, as well as other continental and English writers. Then, full attention is given to those plays of Shakespeare which utilize the Greek materials. The notes are full and, with the aid of the extensive index, can serve as a manual of the Greek romanc.